Carbon Nanotubes with Cobalt Corroles for Hydrogen and Oxygen Evolution in pH 0–14 Solutions. (18th October 2018) - Li, Xialiang; Lei, Haitao; Liu, Jieyu; Zhao, Xueli; Ding, Shuping; Zhang, Zongyao; Tao, Xixi; Zhang, Wei; Wang, Weichao; Zheng, Xiaohong; Cao, Rui
Abstract: Water splitting is promising to realize a hydrogen‐based society. The practical use of molecular water‐splitting catalysts relies on their integration onto electrode materials. We describe herein the immobilization of cobalt corroles on carbon nanotubes (CNTs) by four strategies and compare the performance of the resulting hybrids for H2 and O2 evolution. Co corroles can be covalently attached to CNTs with short conjugated linkers (the hybrid is denoted asH1 ) or with long alkane chains (H2 ), or can be grafted to CNTs via strong π–π interactions (H3 ) or via simple adsorption (H4 ). An activity trendH1 ≫H3 >H2 ≈H4 is obtained for H2 and O2 evolution, showing the critical role of electron transfer ability on electrocatalysis. Notably, H1 is the first Janus catalyst for both H2 and O2 evolution reactions in pH 0–14 aqueous solutions. Therefore, this work is significant to show potential uses of electrode materials with well‐designed molecular catalysts in electrocatalysis.